Safety and adherence of pressure garment therapy in children with upper limb unilateral cerebral palsy. Results from a randomized clinical trial ancillary analysis - Béghin, Laurent; Mohammad, Yasser; Fritot, Séverine; Letellier, Guy; Masson, Sixtine; Zagamé, Yann; Donskoff, Catherine; Toussaint-Thorin, Mathide; Gottrand, Laurence (Frontiers in Pediatrics, 2023)
Background This study was conducted to assess the safety and adherence of the use of a PGT (Pressure Garment Therapy) Lycra® sleeve to treat upper limb unilateral cerebral palsy (UCP) in children. Methods This study was conducted as a prospective, placebo-controlled, double-blinded, randomized monocenter study. Included in the study were 58 UCP children, 49 of whom were analyzed. 25 children (mean age 6.6 ± 1.6 years; 12 girls) were allocated to the active group vs. 24 (mean age 6.7 ± 1.6 years; 10 girls) in the placebo group. The intervention consisted of an active PGT Lycra® arm sleeve manufactured to generate a homogeneous pressure ranging from 15 to 25 mmHg. The placebo PGT Lycra® sleeve was manufactured to generate a homogeneous pressure under 7 mmHg. The time of wearing period was set at 3 h/day at minimum and 6 h/day at maximum, over the course of 6 months. The main outcome measures were safety outcomes including the number and intensity of Adverse Events of Special Interest (AESIs). AESIs were defined as adverse events imputable to compressive therapy and Lycra® wearing. Level of adherence was expressed in percentage of number of days when the sleeve was worn for at least 3 h per day compared to length of duration in days (start and end date of wearing period). Results Frequency of AESIs were very low and no different between groups (4.12 ± 11.32% vs. 1.83 ± 3.38%; p = 0.504). There were no differences in adherence (91.86 ± 13.86% vs. 94.30 ± 9.95%; p = 0.425). Conclusion The use of PGT Lycra® arm sleeve in children with UCP is safe and well-tolerated with a very good adherence. The low rate of AESIs is promising for further randomized clinical trials on efficacy.